2020
DOI: 10.1016/j.yebeh.2020.107351
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral levels of sST2 are increased in patients with temporal lobe epilepsy: Additional evidence of low-grade inflammation

Abstract: Inflammation plays a pivotal role in temporal lobe epilepsy (TLE) pathophysiology. IL-33 can act as a transcription factor or as a cytokine, the latter through the transmembrane ST2 receptor or its soluble isoform (sST2), presenting a dual role in neurological diseases. The aim of this study was to determine the plasma levels of IL-33 and sST2 in parallel with clinical features in patients with TLE. Peripheral blood from patients and controls was sampled for the measurement of plasma levels of IL-33 and sST2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“… 182 Memory performance was also correlated with IL-33 levels in temporal lobe epilepsy. 180 In an animal model of recurrent neonatal seizures, IL-33 administration improved learning, memory, and behavior deficits, as well as body weight gain secondary to seizures by inhibition of apoptosis, endoplasmic reticulum stress, and neuroinflammation. 181 Thus, IL-33 seems to be a new, promising treatment option for reducing the negative impact of recurrent seizures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 182 Memory performance was also correlated with IL-33 levels in temporal lobe epilepsy. 180 In an animal model of recurrent neonatal seizures, IL-33 administration improved learning, memory, and behavior deficits, as well as body weight gain secondary to seizures by inhibition of apoptosis, endoplasmic reticulum stress, and neuroinflammation. 181 Thus, IL-33 seems to be a new, promising treatment option for reducing the negative impact of recurrent seizures.…”
Section: Discussionmentioning
confidence: 99%
“…154 A few studies have identified a relationship between IL-33/ST2 pathway and epilepsy. 153,[180][181][182] Plasma ST2 levels were found higher in patients with increased epileptiform abnormalities after SAH, as well as patients with focal temporal lobe epilepsy. 153,180 Moreover, oxidative stress index, which is significantly higher in patients not responding to antiepileptic drug treatment, was positively correlated with IL-33 levels.…”
mentioning
confidence: 95%
See 1 more Smart Citation